Properties of coated and uncoated biomass aggregates and their effects on the strength and water permeability of pervious geopolymer concrete - Arafa, S.A.; Mohd Ali, A.Z.B.; Abdul Awal, A.S.M.; Shamsuddin, Shamrul-Mar; Hossain, M. Zakaria (GEOMATE International Society, 2018)
Biomass aggregate (BA) is a by-product of biomass industries which is less dense and more porous than natural aggregate. In this two-part study, BA was mixed with fly ash and alkaline liquid, and heated in an oven at 80 °C for 24 h to produce coated biomass aggregate (CBA). The first part of this study was focused on the density, specific gravity, Los Angeles test, water absorption, aggregate impact value, and aggregate crushing value of BA, CBA, and normal aggregates (NA). The second part was focused on compressive strength and water permeability of pervious geopolymer concrete (PGC) that was produced with BA and CBA. Pervious concrete is a non-slip porous pavement concrete that allows water to slip through. In this study PGC was prepared from alkaline solution: fly ash ratio of 0:5, fly ash/coarse aggregate ratio of 1:7, Na2SiO3/NaOH ratio of 2:5, and NaOH concentration of 10 molarity. PGC was cured at 80°C for 24 h. PGC made with CBA had higher compressive strength without much effect on water permeability. It has been found that PGC made with BA and CBA had lower density than PGC made with NA. Results indicated that both BA and CBA are viable alternative aggregates for producing PGC.